William LePre Houston family papers - Houston, William LePre; Houston, Charles Hamilton, 1895-1950.
Correspondence, diaries, financial records, academic papers, printed material, and other papers chiefly of William LePre Houston, a Washington, D.C., lawyer, and his son and law partner, Charles Hamilton Houston. Documents William's work as attorney for the Railway Men's International Benevolent Industrial Association and other African American labor organizations, his activism as a Republican, and his position as grandmaster of the Grand United Order of Odd Fellows in America. Other subjects include Charles's service in the U.S. Army in France during World War I and his education at Amherst College, Amherst, Mass., Harvard Law School, Cambridge, Mass., and the Universidad Central (Spain), Madrid, Spain, and Houston family life. An autograph collection contains signatures of George Washington and Anthony Wayne. Family correspondents include William LePre Houston's wife, Mary Ethel Hamilton Houston, and Charles Hamilton Houston's first wife, Margaret Gladys Moran Houston. Other correspondents include W.E.B. Du Bois, William Hastie, Will H. Hays, G. David Houston, Mordecai W. Johnson, Edward H. Morris, Booker T. Washington, and Carter Godwin Woodson.
Library of Congress Serial and Government Publications Division.
Library of Congress Prints and Photographs Division.
William LePre Houston (1870-1953), lawyer, and his son, Charles Hamilton Houston, also a lawyer.
Collection material in English, with French and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Hastie, William, -- 1904-1976 -- Correspondence; Hays, Will H. -- 1879-1954 -- Correspondence; Houston, G. David -- Correspondence; Houston, Margaret Gladys Moran -- Correspondence; Houston, Mary Ethel Hamilton -- Correspondence; Johnson, Mordecai W. -- 1890-1976 -- Correspondence; Morris, Edward H. -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; Washington, George, -- 1732-1799 -- Autographs; Wayne, Anthony, -- 1745-1796 -- Autographs; Woodson, Carter Godwin, -- 1875-1950 -- Correspondence; Houston family; United States. -- Army -- History -- World War, 1914-1918.; Amherst College; Grand United Order of Odd Fellows in America; Harvard Law School; Railway Men's International Benevolent Industrial Association; Universidad Central (Spain); African Americans; Labor unions, Black -- United States; Practice of law -- Washington (D.C.); Republican Party (U.S. : 1854- ); World War, 1914-1918 -- France; Lawyers